Identification of voltage sag origin in a measurement deficient power network - Mahmood W.N.W.; Mukerjee R.N.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Voltage quality affects the system operation and the customer load operation in a distribution system. To be able to detect existence of sag and identify its cause for determining mitigation options, it is necessary to monitor the system online, to determine the probable origin of the event leading to the voltage sag. It is usual to have power quality related events, more specifically a sag or swell, surfacing at the distribution level due to a fault at the transmission level. However, it may not be possible to provide measurement facilities at each of the buses and lines in a power network, both at the transmission and distribution levels. Based on the measurements available at a single point on a distribution network, the paper suggests a procedure for identifying the location of a single line to earth fault on either the transmission or the distribution portion of the network. 2003 IEEE.